Extra-regional threats to security - Baeza Freer, Jaime; Cortinhas, Juliano; Escudero Illanes, María Cristina; Pastrana Buelvas, Eduardo; Pérez Henríquez, Diego; Jorge Ramalho, Antonio; Rooney Paredes, Mildred; Vera Piñedos, Diego (Pontificia Universidad Católica del Perú. Instituto de Estudios Internacionales (IDEI), 2020)
In 2020, six years after its creation, the Policy Network on Security has produced a new publication titled “Extra-regional threats to security.”1. It is an interesting and important topic in which the Policy Network on Security again seeks to offer its contribution. This policy paper thus concentrates on identifying and analyzing the extra-regional threats, risks and vulnerabilities facing Peru and its neighboring countries. These include the presence in the region of countries such as China, Russia and Iran, their intervention in the Venezuelan crisis and the tensions they generate with the United States; the challenges the Venezuelan crisis represents particularly on migratory, health, economic-social, labor and educational issues; organized crime; cybernetic crimes; the global threat of pandemics such as COVID-19; drug trafficking; illegal mining and logging; contraband; human trafficking; citizen insecurity; corruption and assets laundering; the presence of groups associated with Islamic extremism; lethal autonomous weapons; maritime pirating; and Antarctic claims, among others.
Keywords: Seguridad internacional; Vulnerabilidades extraregionales; https://purl.org/pe-repo/ocde/ford#5.04.05